2022
DOI: 10.12688/hrbopenres.13307.3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the utilisation of acute hospital care in Ireland during the first wave of the COVID-19 pandemic in 2020

Abstract: Background: Reduced and delayed presentations for non-COVID-19 illness during the COVID-19 pandemic have implications for population health and health systems. The aim of this study is to quantify and characterise changes in acute hospital healthcare utilisation in Ireland during the first wave of COVID-19 to inform healthcare system planning and recovery. Methods: A retrospective, population-based, observational study was conducted using two national datasets, Patient Experience Time (PET) and Hospital In-Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Interestingly, the two time points contained a high proportion of institutional process complaints, with this being the most common HCAT category used to classify the complaints in both Q4 2019 and Q4 2020. Despite the large systemic changes that occurred as a result of the pandemic (1), patients continued to complain about bureaucratic issues and waiting times in similar proportions, indicating that these problems did not disappear despite the reduced numbers attending hospitals during the COVID-19 pandemic [7]. A recent national study of Irish hospitals also found that institutional process issues were the predominant HCAT category in complaints from Q4 of 2019 [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the two time points contained a high proportion of institutional process complaints, with this being the most common HCAT category used to classify the complaints in both Q4 2019 and Q4 2020. Despite the large systemic changes that occurred as a result of the pandemic (1), patients continued to complain about bureaucratic issues and waiting times in similar proportions, indicating that these problems did not disappear despite the reduced numbers attending hospitals during the COVID-19 pandemic [7]. A recent national study of Irish hospitals also found that institutional process issues were the predominant HCAT category in complaints from Q4 of 2019 [25].…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to reduce the spread of the virus, such as lockdowns, the migration to virtual healthcare consultations, the cancellation of elective care, and visitor restrictions, all impacted normal healthcare delivery [1,3]. Healthcare staff experienced immense pressure during the early stages of the pandemic, with limited initial knowledge about the features of the virus or its transmission, a shortage of appropriate personal protective equipment (PPE), and the psychological strain of treating patients who were very sick with COVID-19 [4][5][6][7]. Two years on from the beginning of the pandemic, the true extent of the impact the virus has had on the safety and quality of care provided to patients is beginning to be understood [8,9].…”
Section: Introductionmentioning
confidence: 99%